IMPLEMENTASI RINGKAS, RAPI, RESIK, RAWAT,DAN RESIK (5R) DI PT. PSE PRIMA SUKSES - Nur Aviva; Farah Nur Fauziah; Maskur (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2022)
The aim of this research is to describe how 5R activities are implementedbefore and after 5R enters PT PSE Prima Sukses. This company uses a 5Sculture so that the company environment is concise, neat, clean, wellmaintained and clean, where all employees participate in carrying out theseactivities. These regulations are regulated in accordance with the regulationsthat have been established by the company, where the 5R activities arecarried out in a structured manner with the formation of an AKK chairman ineach production line, in the form of picket members every day, with theformation of the committee to make it easier for 5R activities to run easilyand run more conducively Before the 5R program was only the responsibility of each individual, after the 5R program all employeesparticipated in the 5R activity program. Apart from that, having 5S activitiesin the production area can benefit the company if the 5S are implementedwell and can increase production productivity.